PSXV-11 Modulation of bacterial composition in the gastrointestinal tract of calves fed Lactobacillus acidophilus during the early period of growth. (7th December 2018) - Fomenky, B; Do, D; Talbot, G; Bissonnette, N; Lessard, M; Chouinard, Y; Ibeagha-Awemu, E
Abstract: Direct-fed microbials (DFM) like Lactobacillus acidophilus (LA) can influence the composition of the gastrointestinal tract (GIT) microbiota of ruminants resulting in beneficial effects on health and productivity. In this study, the GIT microbiota of 16 calves (8/treatment) fed LA BT1386 (2.5 × 10 8 CFU/L milk replacer + 1 × 10 9 CFU/kg starter feed) or not supplemented (CTL) were investigated. Eight calves (4/treatment) were euthanized on day33 (pre-weaning) and another group (4/treatment) on day96 (post-weaning) to collect rumen (RuD), ileum (IlD) and colon digesta (CoD), and ileum (IlM) and colon mucosa (CoM) samples. Extracted DNA was subjected to 16S rRNA gene amplicon sequencing (Illumina MiSeq) followed by bioinformatics analysis using QIIME. The PICRUStsoftware was used for the prediction of functional genes. Differential abundance of genera between LA and CTL was examined using DESeq2 package in R program. A comparison between LA and control was done within each GIT site on day33 (pre-weaning) and day96 (post-weaning) separately. Pre-weaning, three and 18 genera were affected (P<0.05) by LA in CoM and IlM while no genus was affected in RuD, IlD and CoD compared to CTL. Fibrobacter genus was increased (p.FDR=3.09E-02) in IlM while Tyzzerella_4, Ruminococcaceae_UCG-008 and Lachnoclostridium were significantly reduced (p.FDR≤1.67E-06) in IlM by LA compared with CTL. Post-weaning, LA treatment impacted the relative abundance (p.FDR<0.01) of five general (Ruminococcus_2, Lactobacillus, Ruminiclostridium_9, Prevotella_1 and Acetitomaculum ) in IlD. LA was predicted to impact four pathways (caffeine metabolism, cAMP signaling, steroid biosynthesis, proteasome/dopaminergic synapse pathways) in RuD pre-weaning and caffeine metabolism pathway in CoM and cell cycle, EGFR tyrosine kinase inhibitor resistance, oxytocin signaling pathway, mRNA surveillance pathway, and fanconi anemia pathways in IlM post-weaning, compared to CTL (P<0.01). This study provides insights on potential mechanisms by which LA modulated the GIT microbiota and may therefore facilitate the development of DFMs for use in dairy calf.